EVALUASI PEMAKAIAN BAHASA INDONESIA DALAM KARYA ILMIAH DI PERGURUAN TINGGI NEGERI MEDAN - Amran Purba (MEDAN MAKNA: Jurnal Ilmu Kebahasaan dan Kesastraan, 2018)
This research is a normative research about evaluation language used in scietific works (thesis) at state universities in Medan. This research aims to create the used of standardized and welformed Indonesian language at university students, even at state or private universities in Medan with national standard for scientific works. To applicate that the book of Ejaan, Diksi, Istilah, Kalimat, dan Pernalaran is used (Moeliono et al., 2001) dan (Alwi et al., 2001). The research uses survey with descriptive qualitative and quantitave to find actual uptodate, and factual language data by doing scientific writing research at state universities in Medan. This research uses coding and directed observation techniques in using scientific writing of Indonesian language at IAIN, UNIMED, USU libraries. This choosen domain based on that the domain is assumed influencing university students language in North Sumatera. Therefore, the presented data is language phenomena and image at university student scientific language in Medan. The result of this research shows that Indonesian langugae used at thesis has many mistakes or errorness, such as spelling system, conjunction, sentence structure and interpretation, thus morphemes, dictions, and terms.